Understanding the structure, experiences and challenges of social support for older lesbian, gay and bisexual people: a systematic review. Issue 2 (28th August 2018) - Hawthorne, Oliver; Camic, Paul M.; Rimes, Katharine A.
Abstract: The psycho-social contexts of older lesbian, gay and bisexual (LGB) individuals suggest that they may face unique strengths and barriers in accessing social support. The present review aimed to explore what is known about this by providing a synthesis of this area of research and a methodological critique. The Applied Social Sciences Index (ASSIA), Psychinfo and Medline databases were searched and 22 relevant articles were identified. Key findings were extracted and quality was assessed using a standardised rating scale. The findings indicated that although many older LGB people report similar-sized support networks to older heterosexuals, more support came from friends and less from biological family members. Many reported not receiving enough support; it is possible that differences in care-giving between friends and family and anticipated social support difficulties due to previous LGB-stigma experiences partially account for this. Current recruitment strategies may mean that more-connected older LGB people are over-represented in research. There is a lack of research with the 'old-old' population, bisexual people, those with significant health needs, those outside the United States of America and those with additional characteristics associated with discrimination. Practical and research implications are discussed and it is suggested that friendship–carer dyads may need support to have more explicit discussions about care-giving roles due to a lack of societal templates for these kinds of relationships.